Response of wheat to applied soil potassium in soils differing in available potassium status under irrigated conditions - KAUR, HARPREET; GILL, R.S.; DHERI, G.S.; SAINI, S.P. (Journal of Soil and Water Conservation, 2024)
A field experiment was conducted at Ludhiana (medium in available K) and at Gurdaspur (low in available K) during Rabi season 2018-19. Effect of applying eight levels of K (0 to 40 kg K ha-1 soil) on grain yield of wheat at both the sites revealed that the significant response of wheat to application of K up to 40 kg K ha-1 were confined to low in available K, however, in K sufficient soil, it was recorded only up to 25 kg Kha-1. The mean grain yield increased by 18.9 % and 35.7 % in soil of PAU, Ludhiana and RRS Gurdaspur, respectively with the highest level of applied K. The percent increase in exchangeable and non exchangeable K with increasing level of K application was higher in PAU, Ludhiana soil as compared to RRS, Gurdaspur soil. Therefore, the yield and K content of both grain and straw were found higher at all the levels of applied K in K sufficient soil as compared to K deficient soil. The current study reflects that the soil with sufficient amount of plant available K can supply adequate amount of K the crop does not respond to higher doses of K, whereas, on K deficient soil, crop will require high rates of K fertilizers to maintain adequate nutrition.